ANALISIS PENGUKURAN WAKTU PELAYANAN TRUCK ROUND TIME DENGAN VALUE STREAM MAPPING - Putri Rahmadhani; Devina Puspita Sari; Yugowati Praharsi (Proceeding Maritime Business Management Conference, 2024)
Container depots serve as distribution centers connecting manufacturers to consumers viamaritime routes. To enhance service quality, this research aims to measure the service timesinvolved in the container reception and delivery processes at the depot. The analysis isconducted by collecting time data through direct observation and interviews with relevantstakeholders. One methods utilized is value stream mapping. focusing on identifying nonvalue added activities within the container transfer process. The study reveals significant leadand cycle times for various activities: during the receiving phase, the lead time recorded is2,514.43 seconds with a cycle time of 1,262.35 seconds, while the delivery phase shows alead time of 2,280.21 seconds and a cycle time of 1,301.89 seconds. Through VSM, theanalysis highlights inefficiencies in the container transfer process, emphasizing areas wherenon-value added activities contribute to delays and increased operational times. Bypinpointing these inefficiencies, the study aims to provide actionable insights to streamlineprocesses, reduce lead and cycle times, and enhance overall operational efficiency at thedepot.